IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING DOMINO CARD GAME - Muhammad - Ridho Arfansya; maliqul - hafis; Dian - Shinta Sari (IKIP PGRI Pontianak, 2023)
In order to teach vocabulary mastery through the dominos card game to eight students in grade eight at SMP Negeri 03 Sungai Raya for the academic year 2022/2023, the purpose of this study is to determine how the domino card game can improve students' vocabulary mastery and the classroom environment when playing dominoes is applied. Class action research was used to carry out this study (CAR). The eighth grade of SMP Negeri 03 Sungai Raya, which had 33 pupils, was the focus of this study. Techniques for gathering data for this study included measurement and observation. Measurement approaches use language exams, while observation techniques use observation checklists and field notes. The study's data analysis then employs both qualitative and quantitative methods, depending on the type of data being analyzed The researcher measured students' vocabulary mastery through domino card games using two methods of assessment: individual scores and average scores. With the help of domino card games, the children were more engaged in the vocabulary acquisition process. They then showed greater enthusiasm for learning vocabulary through domino card games. The usage of domino card games can raise student results on the vocabulary test, as seen by cycle 1's low student scores (average score: 75.36) and cycle 2's higher student scores (average score: 81.36). The researcher advises other teachers to use domino card games while instructing pupils in vocabulary proficiency. The domino card game is a fun way to engage kids in the teaching and learning process while also helping to increase their vocabulary proficiency. Keywords: Classroom Action Research, Vocabulary Mastery, Domino Card Game